Building Design Mlatiharjo Urban Village PKK Administration Governance System East Semarang Sub-District - Listiarini Edy Sudiati; Gilang Pandu Susandi; Ninik Haryani; Daniel Alfa Puryono (PT FORMOSA CENDEKIA GLOBAL, 2023)
PKK as a partner of the lurah government is the closest community organization to the family and plays an important role in empowering and improving family welfare. PKK is divided into 4 working groups: Working Group (POKJA) 1 manages the Pancasila and Gotong Royong Program, Working Group 2 manages the Education and Skills Program and the Development of Cooperative Life, Working Group 3 manages food, clothing, housing and household management programs, Working Group 4 manages health programs, environmental sustainability and healthy planning. In order to support the duties of the TP PKK secretary to manage PKK administration and report and evaluate PKK work programs, according to Shinta Esabella et al (Esabella et al., 2022) in their research, it is necessary to design and build a Web-based Administrative Governance Information System. The governance of the PKK administration in Mlatiharjo Village, East Semarang District is still done manually, both for work programs, financial reports, annual reports and correspondence management. With this manual system, it will make it difficult for the PKK secretary to distribute work programs, collect data, manage documents, correspondence and make reports. With these problems, researchers conducted research with the aim of building a PKK administrative governance system for Mlatiharjo Village, East Semarang District. The research method is qualitative analysis, the system development method is RAD and uses UML tools. The research output is the design of the PKK administration governance system